Efektivitas Handrub Berbasis Alkohol Sama dengan Hypochlorous Acid dengan Waktu Kontak yang Berbeda - Masfiyah, Masfiyah; Rahayu, Rahayu; Bellarinatasari, Nika (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
HAIs (Healthcare-Associated Infections) cause mortality, morbidity, prolonged hospitalization, and economic losses. HAIs can be prevented by good hand washing. Washing hands with alcohol has been shown to be effective in killing microorganisms. Alcohol as a halal handrub is used, but some are still concerned about its halalness. This study aims to compare the killing ability of hypochlorous acid-based handrub for 60 seconds compared to alcohol for 20 seconds. This research was an experimental study with a pretest-posttest design with a control group. The research was conducted at the Integrated Biomedical Laboratory of FK Unissula. The study population consisted of 7 janitors and security officers who had previously been trained in washing hands using WHO's 6 steps (20 seconds). The alcohol used was made based on the WHO formulation, while the hypochlorous acid used was at a concentration of 110 ppm. Preliminary research was conducted to determine the contact time of hypochlorous acid, the result was 60 seconds. Tests were carried out on the number of bacteria on the hands before and after washing hands using hypochlorous acid and alcohol. The percentage decrease in the number of colonies between pre and post between the two groups was analyzed using the Mann-Whitney U test. The result of the percentage reduction of colonies that grew on nutrient agar medium, alcohol compared to hypochlorous acid was p = 0.084. Most of the microorganisms are gram positive, dominated by Bacillus sp and Coagulase negative Staphylococcus. Hypochlorous acid-based handrub has the same effectiveness as alcohol in killing microorganisms.Keywords: alcohol; hypochlorous acid; effectiveness ABSTRAK HAIs (Healthcare-Associated Infections) menyebabkan mortalitas, morbiditas, rawat inap memanjang, dan kerugian ekonomi. HAIs dapat dicegah dengan cuci tangan yang baik. Cuci tangan menggunakan alkohol terbukti efektif membunuh mikroorganisme. Alkohol sebagai handrub halal digunakan, tetapi beberapa masih khawatir tentang kehalalanmya. Penelitian ini bertujuan untuk membandingkan kemampuan membunuh handrub berbahan dasar hypochlorous acid selama 60 detik dibandingkan alkohol selama 20 detik. Penelitian ini adalah penelitian experimental dengan rancangan pretest-posttest with control group. Penelitian dilakukan di laboratorium Biomedik Terintegrasi FK Unissula. Populasi penelitian adalah petugas kebersihan dan petugas keamanan sebanyak 7 orang, yang sebelumnya sudah dilatih cuci tangan menggunakan 6 langkah WHO (20 detik). Alkohol yang digunakan dibuat berdasarkan formulasi WHO, sedangkan hipochlorous acid yang digunakan dengan konsentrasi sebesar 110 ppm.  Penelitian pendahuluan dilakukan untuk mengetahui waktu kontak hipochlorous acid, didapatkan hasil 60 detik. Dilakukan pengujian tentang jumlah bakteri pada tangan sebelum dan sesudah cuci tangan menggunakan hypochlorous acid dan alkohol. Persentase penurunan jumlah koloni antara pre dan post antara kedua kelompok dianalisis dengan menggunakan Mann-Whitney U test. Hasil persentase penurunan koloni yang tumbuh pada medium nutrient agar, alkohol dibandingkan hypochlorous acid adalah p = 0,084. Sebagian besar mikroorganisme adalah gram positif, didominasi oleh Bacillus sp dan Coagulase negative Staphylococcus. Handrub berbasis hypochlorous acid mempunyai efektivitas yang sama dengan alkohol dalam membunuh mikroorganisme. Kata kunci: alkohol; hypochlorous acid; efektivitas